Intergenerational Educational Mobility within Chile - Muñoz, Ercio (Estudios de Economía, 2025)
I provide estimates of intergenerational mobility (IGM) in education at a disaggregated geographic level for Chile, a country with high school-level stratification by socioeconomic status and a decentralized administration of public schools. I document wide variation across municipalities. Relative mobility is correlated to the number of doctors, the number of students per teacher, and earnings inequality. Using a LASSO, I find that the share of students enrolled in public schools, the number of students per teacher, population density, and municipal budget are the strongest predictors of IGM. I also document within-country variability in how parental education is associated with other children’s outcomes